Rational Design of an IoT-Based Automated Mini Maggot Farm for Optimizing Organic Waste Management - Adi Purnama Syukri; Muhammad Anwar (Takaza Innovatix Labs Ltd., 2024)
This The increasing volume of household and market organic waste has become an environmental issue that requires effective and sustainable solutions. Cultivating Black Soldier Fly (BSF) maggots is one method capable of reducing organic waste while producing economically valuable products. However, traditional maggot cultivation still faces challenges in maintaining environmental conditions such as temperature, humidity, air quality, and inconsistent feeding schedules. This study aims to design and implement an Internet of Things (IoT)-based automated mini maggot farm to optimize organic waste management. The research method used is the Waterfall model, which includes planning, analysis, design, implementation, and system testing stages. The system utilizes an ESP32 microcontroller as the main controller, a DHT22 sensor for monitoring temperature and humidity, an MQ-135 sensor for detecting air quality, and an RTC DS3231 module for automated feeding schedule management. Additionally, the system is equipped with actuators such as fans, heaters, and servo motors that operate automatically based on environmental conditions. The system monitoring is conducted in real-time using the Blynk application and local display through an LCD. The testing results indicate that the system operates stably and is capable of monitoring and controlling the mini maggot farm environment automatically. The implementation of this system improves efficiency and consistency in maggot cultivation compared to manual methods. Therefore, the IoT-based automated mini maggot farm can serve as an effective solution for optimizing organic waste management and supporting sustainable smart farming practices.